Social Protection Rights For The Elderly In Medan Amplas District According To Law No. 13 1998 And Islamic Law - Uswatun Hasanah (AT-TAFAHUM: Journal of Law, 2018)
The studies about "The Rights of Social Protection for Aged in Medan Amplas based on Law No. 13 of 1998 and Islamic Law". The study will investigate how is the implementation of the rights of social protection for aged in Medan Amplas based on Law No. 13 of 1998, how is the implementation of the rights of social protection for aged in Medan Amplas based on Islamic Law and what is the problem and solution in implementing the social protection for aged in Medan Amplas. The findings showed that the rights of social protection for aged in Medan Amplas were not fulfilled properly. It was based on the information which had been obtained from the Social Services of Medan and also the observations and interviews which had been carried out. They were the right to get ASLUT (The social assistance for Aged) and PKH (The Prospects of Family Program). Most of the elderly did not get those kinds of aid. Moreover, there were only 175 aged who got the ASLUT in Medan. The information has been found that the limitation of funds from the government caused the rights for most aged did not fulfill well. The case can be a good input for the government to increase the funds for the elderly to fulfill their rights of social protection